Determination of Technical Specifications for a Digital QR Code System Using Axiomatic House of Quality for Error Prevention - Wulung Aditya; Ni Luh Putu Hariastuti (Jurnal Teknologi dan Manajemen, 2026)
This study aims to determine the technical specifications of a digital QR Code system for the weighing process of practical spice powder recipes using Axiomatic House of Quality to prevent human error. User requirements data were collected from 25 respondents and validated through a Focus Group Discussion (FGD) involving 9 technical experts. The results identified 14 Customer Attributes (CA), which were subsequently translated into 14 Design Parameters (DP). Design matrix analysis indicated that the system is categorized as an uncoupled design, where each Functional Requirement corresponds to a specific DP, thus maintaining the independence of functions and design parameters. The resulting technical specifications are practical and applicable, covering hardware components, user interface, alarms, data storage systems, and material detection mechanisms. Therefore, the designed digital QR Code system can prevent weighing errors caused by human error and enhance product quality from the consumer’s perspective